Competencies of vocational teacher: a personnel measurement framework - Arifin, Muhammad Aiman; Mohd Rasdi, Roziah; Mohd Anuar, Mohd Ashraff; Omar, Muhd Khaizer (Human Resource Management Academic Research Society, 2017)
Recently, Transforming Technical Vocational Education and Training has been strategized by the Malaysian government to meet the industry demand and future economic growth. In the context of competency-based human resources and vocational education, the purpose of this study is to identify and map competencies for effective job performance required for vocational teachers towards developing a competency model and the measurement instrument. Discussion in this study gathered through related literature review of this competency and vocational teaching profession. The proposed measurement model for vocational teacher builds on the four competency domains namely “teaching competence”, “professional competence”, “communication competence” and “personal competence”. Once the model and measurement instrument tested for robustness on the psychometrics properties, it could be a reference among HR researcher and practitioner in designing the new curricula and training for professional development. Hence, the proposed personnel measurement model in this study would differentiate from other teacher competencies and provide new insights on individual effective job performance specific for vocational teaching profession.